Corrigendum: Imprint of climate change on Pan-Arctic marine vegetation - Krause-Jensen, Dorte (2021)
In the original article, there were mistakes in Tables 2–4 and associated legends and text as published. The original article contained errors in the reported modeled macroalgal distribution area in the pan-Arctic and its subregions because the polygons used to calculate the areas were not correctly defined. A correction has been made to Tables 2–4 and their associated legends: The Table legends missed the word “brown” and an explanatory note. The corrected Tables 2–4 and associated legends appear below (corrections marked in bold).